The Role of Livelihood Diversification and Social Capital in the Movement of Households: A Case Study from Central Nepal - Pokharel, Saroj; Tharu, Dipak; Pandey, Yagya Murti (South Asian Journal of Social Sciences and Humanities, 2021)
The study aims to investigate the role of livelihood diversification and social capital for the households’ movement, and also to explore the identity and bond of social capital and livelihood diversification to achieve an improved lifestyle. Human relations significantly create a network society, impalpable resource of community, shared values and trust which we draw upon in our daily lives. Livelihood diversification is a community-practised strategy for managing economic and income diversity in poverty reduction. It has highly emphasized income and well-being to diversify livelihood. It also turns the likely norms and networks with the households from exploiting new economic opportunities even in the future. This study responds to why people are migrating from the surrounding and the long distance of Kathmandu, and largely dependent on direct cash incomes from informal activities. It used qualitative approaches such as ethnography, case studies, participant observation, etc. to study the relationship between households and social capital level and livelihood diversification. Hence, the effects of social capital and livelihood diversification were found protecting households’ income. The major findings also show the social supportive network index which has significant effects on the households' ability to learn a new livelihood. Income generations similarly affect the household capacity to secure a home and the socio-economic condition of households. This study can be advantageous for making both local and urban policy to diversify household livelihoods and social capital as well as applicable for new researchers in social sciences. Most importantly, it helps readers perceive new ways of promoting livelihood diversification and social capital and as a whole social advancement in Central Nepal.
Keywords: Income Diverse; Livelihood Diversification; Migration; Social Network; Social Capital.